دور اللغة الملايوية الوطنية في التعددية اللسانية بماليزيا وأبعادها الإسلامية (The role of the national Malay language in Malaysia's linguistic pluralism and its Islamic Dimensions) - شحادة علي, عاصم (Journal of Islam in Asia (E-ISSN 2289-8077), 2022)
تعد اللغة الوسيلة المؤثرة في تشكيل السلوكيات الفردية والجماعية للطوائف المتعددة في مجتمع ما، ولذلك نجد أن اللغة الوطنية بماليزيا تؤدي دورا حيويا في عملية الاتصال بين هذه الطوائف المتنوعة كطائفة الملايو (وهم أهل البلد الأصليين)، وطائفة الصينيين، وطائفة الهنود (التاميل)، وكذلك تؤدي اللغة الوطنية دورا مهما في الوحدة الوطنية بين الطوائف من أجل تحقيق شعار (ماليزيا واحدة) الذي تبنته الحكومة الماليزية في كل المجالات ومنها اللغة، وتستخدم هذه اللغة في المعاملات الرسمية في المؤسسات الحكومية، والشركات المحلية والوزارات المختلفة، والتواصل بين أفراد المجنمع الماليزي المتعدد الطوائف. في ضوء هذا سوف تقوم الدراسة بتتبع أوضاع اللغة الملايوية قبل الاستعمار البريطاني وبعد استقلال ماليزيا عام 1957م، والبحث عن اللغات المتداولة في المجتمع الماليزي كالصينية والتاميلية وغيرها كاللغة العربية عبر برنامج (جي قاف) وتطبيقه في المدارس الحكومية لتحقيق الوحدة بين الملايو أنفسهم، وبيان استخدام اللغة الملايوية في المدارس الحكومية الوطنية وفي المؤسسات التعليمية، والصعوبات التي واجهت اللغة الملايوية بوصفها لغة رسمية في المعاملات، وتحمل اللغة الملايوية الأبعاد الإسلامية، وتتبع عمليات تحسين أوضاع اللغة الملايوية بين الماليزيين على اختلاف طوائفهم، والإجراءات التي اتخذت لجعل الملايوية لغة وطنية جامعة سياسيا واجتماعيا في مجتمع التعددية اللسانية كماليزيا. .الكلمات المفتاحية: اللغة الماليزية، تعليم الملايوية، تطور التعليم، اللغات المستعملة Abstract Language has its influence in forming the individual and collective behaviours of communities in a society. The national language in Malaysia plays a vital role in the communication process between a community of Malays (who are the country's indigenous population), Chinese, and Indian (Tamil). The national language plays an important role in the national unity between the communities to achieve the slogan (One Malaysia), which was adopted by the Malaysian government in many aspects including the language. This Malay Language is used in official transactions in government institutions, local companies, the various ministries, and as a communication between multi-ethnic society of Malaysian. In light of this, the study will track the situation of Malay language before the British colonial rule and after the independence of Malaysia in 1957. It will search about the languages ​​spoken in Malaysian society, as Chinese, TTamil, and other languages such as Arabic which is taught through the (j-QAF) programme in government schools. The study will talk about the situation of the Malay language; the difficulties faced in using Malay as official language, and theIslamic dimensions and identity that it bears as well as the steps taken to improve the use of Malay language between Malaysian people to unite between them politically and socially in the community of multi-lingual such as Malaysia. Keywords: The Malaysian language, Malay education, The development of education, The languages used.